Praktik Jasa Penitipan Mobil di Rusunawa Tanah Merah Utara Surabaya menggunakan Teori Sadd Al-Dhariah - M. Faizal Fiqih (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
The practice of car care services in Rusunawa Tanah Merah Utara Surabaya is a service practice that uses an ijarah contract in accordance with the pillars and conditions of ijarah in Islamic law. However, the practice of custodial services has paved the way for fraudulent service actors, fraud in the results of service payments obtained every month. Due to the initial agreement between the person in charge of the care service and the manager and all residents of the flat, 60% of the income from the service goes to the flat cash and 40% is for the person in charge of the care service. However, the fact is that the results obtained by the person in charge of the care services are greater than the cash yields of the flats, this is not in accordance with the initial agreement. Then there is the negligence of the person in charge of the care service which results in losses for the car owner. In Sadd al-Dhari'ah theory, this kind of ijarah is not allowed and must be prevented. So that, the person in charge of the care service should pay attention to the agreement that has been agreed, be responsible for his duties with trust. For managers and other internal residents of the Flats, they should participate in monitoring the performance of the care services. Car owners should give a warning to the caretaker so that they are professionally responsible.